2019
DOI: 10.1021/acsami.9b08462
|View full text |Cite
|
Sign up to set email alerts
|

Isomerically Pure Benzothiophene-Incorporated Acceptor: Achieving Improved Voc and Jsc of Nonfullerene Organic Solar Cells via End Group Manipulation

Abstract: Benzene-based 1,1-dicyanomethylene-3-indanone (IC) derivatives have been widely utilized as the end-group to construct acceptor−donor−acceptor type nonfullerene acceptors (A−D−A type NFAs). The extension of the end-group conjugation of nonfullerene acceptors (NFAs) is a rational strategy to facilitate intermolecular stacking of the end-groups which are responsible for efficient electron transportation. A bicyclic benzothiophene-based end-group acceptor, 2-(3-oxo-2,3-dihydro-1H-benzo[b]cyclopenta [d]thiophen-1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 57 publications
0
31
0
Order By: Relevance
“…The technique adopted for the fabrication of organic solar cells and their characterization is described in the ESI. † 48 DTCCIC-4F, 49 DTCCIC, 49 DTCC-BC, 50 DTCC-IC, 50 H2FCN-C16, 51 ICz-Rd2, 52,53 ICz-RdCN2, 53 and SMDPP. 54 This selection is based on the best ones where the carbazole residue is employed as a sub-fragment of the nonfullerene acceptor.…”
Section: Materials Device Fabrication and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique adopted for the fabrication of organic solar cells and their characterization is described in the ESI. † 48 DTCCIC-4F, 49 DTCCIC, 49 DTCC-BC, 50 DTCC-IC, 50 H2FCN-C16, 51 ICz-Rd2, 52,53 ICz-RdCN2, 53 and SMDPP. 54 This selection is based on the best ones where the carbazole residue is employed as a sub-fragment of the nonfullerene acceptor.…”
Section: Materials Device Fabrication and Characterizationmentioning
confidence: 99%
“…Among the donating group, carbazole-containing residues have attracted significant attention. [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Over the past two years, the molecular design of carbazole-based NFSMAs has evolved and several examples are presented in Fig. 1 along with the reported PCEs of their BHJ-PSCs (optimized values).…”
Section: Introductionmentioning
confidence: 99%
“…For example, DTCC‐BC , end‐capping the DTCC core with α‐BC, affords its best PCE of 10.74% with PBDB‐T . [ 22 ] Other DTTC‐based NFAs with the same end groups but different side chains, such as DTCCIC and DTCCIC‐4F , showed no better photovoltaic performance than DTCCIC‐C17 and DTC(4Ph)‐4FIC did. [ 23 ]…”
Section: Photovoltaic Performancementioning
confidence: 99%
“…In any case, photovoltaic efficiencies were over 10%. Last year, Chang et al [53] reported the synthesis of a novel NFA, b8, which contains a 2-(3-oxo2,3-dihydro-1H-benzo [b]cyclopenta[d]thiophen-1-ylidene) (α-BC) moiety as the electron-deficient end-capping group. B8 showed similar absorption properties with respect to b0.…”
Section: Modification Of Electron-deficient End-capping Groupsmentioning
confidence: 99%